GitHub Advanced Security Cert Prep by Microsoft Press. - Warner, Tim; Press, Microsoft (linkedin.com, 2024)
Unlock your DevOps potential and prepare to ace the GitHub Advanced Security certification exam with this laser-focused training course—where real-world expertise meets exam mastery.